Analisis Kelemahan Penerapan Kesantunan Berbahasa Anak Usia Dini - Muthie, Imam; Pratiwi, Nanda; Sujarwo, Sujarwo; Ramelan, Harlina; Husna , Amalia; Ulni, Elvira Khori; Novera, Wulan Rahmadia (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2025)
This study aims to analyze the weaknesses in the implementation of language politeness among early childhood learners. Language politeness, closely linked to courteous behavior, is essential for children's social interactions and acceptance. Disruptions in the use of polite language may hinder children's ability to build positive relationships. Politeness traditions, deeply rooted in Indonesian culture, emphasize the importance of respectful communication in daily life. Employing a qualitative descriptive approach, this study involved parents, teachers, and school principals as research subjects. Data were collected through in-depth interviews, observations, and documentation, and validated using triangulation techniques. The findings indicate that five key factors contribute to the weakness of language politeness in early childhood: parental dependence, lack of home supervision, shortcomings in the school environment, children's weaknesses, and the influence of learning media. The study underscores the importance of collaboration among parents, educators, and the community in fostering polite language development. Strengthening politeness values within educational curricula and optimizing the use of supportive learning media are recommended as strategic efforts to enhance language politeness among young children.